β-catenin and Its Relation to Alveolar Bone Mechanical Deformation – A Study Conducted in Rats With Tooth Extraction - Ferreira, Beatriz Carmona; Freire, Alexandre Rodrigues; Araujo, Rafael; Amaral-Silva, Gleyson Kleber do; Okamoto, Roberta; Prado, Felippe Bevilacqua; Rossi, Ana Cláudia (Frontiers in Physiology, 2020)
The aim of this study was to analyze the relationship between alveolar bone deformation and β-catenin expression levels in response to the mechanical load changed by dental extraction in adult rats. Twenty-four male rats (Rattus norvegicus albinus), Wistar linage, at 2 months of age, were used. The right upper incisor tooth was extracted, and euthanasia occurred in periods 5 (n = 6), 7 (n = 6), and 14 (n = 6) days after Day 0. In the control group (n = 6), the dentition was maintained. The euthanasia occurred within 14 days after day 0. After euthanasia, the rats of all groups had their left jaw with tooth removed and separated in the middle. The pieces were undergone routine histological processing and then the immunohistochemical marking were performed to label expression of the primary β-catenin antibody, which was evaluated by qualitative and quantitative analysis. One head by each group (control and experimental) was submitted to computerized microtomography. After the three-dimensional reconstruction of the skull of the rat in each group, the computational simulation for finite elements analysis were performed to simulate a bite in the incisors. In finite element analysis, the strain patterns were evaluated after the application of bite force. The results were analyzed considering the areas in which changes in the amount of deformations were detected. The action of the bite force in the experimental condition, resulted in a uniform distribution of the amount of deformations, in addition to lower amount of deformation areas, differentiating from the control group. Comparing with the control group, the levels of β-catenin signaled in the lingual bone of the middle third of the alveolar bone were raised in the periods of 5 and 14 days. The increased β-catenin positive staining intensity was concentrated on osteocytes and gaps of osteocytes. The findings of the present study were in accordance with our hypothesis that the condition of dental extraction can cause the expression of β-catenin and alter the regimes of bone deformation.